Influence of a mesogenic dendrimer on the morphology of polymer-fullerene composites for photovoltaics - Kasdorf, Olga; Kitzerow, Heinz-Siegfried; Lenoble-Zwahlen, Julie; Deschenaux, Robert (My University, 2010)
The efficiency of bulk heterojunction-type plastic solar cells depends on the morphol. of an entangled network of 2 immiscible compds. that serve as electron donor and electron acceptor. Results are presented on how the luminescence and the morphol. of a composite contg. a fullerene C60 deriv. and a p-phenylene vinylene (PPV) deriv. are altered, when a dendrimer with a fullerene core and mesogenic side-chains, is added. Fluorescence quenching and surface topog. of the composites indicate that adding the mesogenic dendrimer can result in smaller domain sizes, which may be useful for photovoltaic applications. [on SciFinder(R)]
Keywords: mesogenic dendrimer morphol polymer fullerene composite solar cell